(untitled) (International Journal of Engineering and Computer Science, 2016)
The research work on this paper aims to develop an unmanned aerial vehicle equipped with modern technologies various civil military applications. It is an automatic system The shrinking size and increasing capabilities of microelectr-onic devices in recent years has opened up the doors to more capable autopilot and pushed for more real time UAVs applications. The Unmanned Aerial Vehicle (UAV) market is to grow dramatically by 2020, as military, civil and comercial applications continue to develop. Potential changes in air traffic management include the creation of an information It defines a UAV to be ”An aircraft which is management system to exchange information among Air Traffic Management users and providers, the introduction of navigation, and the development of alternative separation procedures. The impact of each scenario on the future air traffic and surveillance is summarized, and associated issues identified. The paper concludes by describing the need for a UAV roadmap to the future. This paper aims to provide a simple and low-cost solution of an autonomous aerial surveyor which can do aerial surveillance ,recognize and track various objects, able in making simple 3d map .